Prosa de ficção contemporânea: os reflexos do golpe militar de 1964 em A festa, de Ivan Ângelo - (:unkn) unknown (Universidade Federal de Goiás, 2019)
The present inquiry is based on the proposal of reading of the novel A Festa (1976), of Ivan Ângelo, by the slant of the interface between the History and the Fiction. The military dictatorship of 1964 is inserted in the narrative in which we look to analyse, for so much, we look to think the prose of fiction of Ivan Ângelo as element metafcicional that inserted the glance of the reader on the factual History – the military blow of 1964. For so much, this inquiry is that it divides in three parts, the first one that can be considered a preamble, in which we do a bibliographical revision and discuss points is intersplit up by you in order that we deepen in the second part, what is shaped like a continuation of the preamble, in which we talk about the view of the contemporary Brazilian literature, and for end, the last part in which two previous are and the forks of analyses of the prose of fiction of Ivan Ângelo, they are pointed, from the interface between the History and the Fiction, the subject of our inquiry. We have like critical-theoretical support, some voices that talk to our object and our proposal of analysis, such as: Gaspari (2002), Benjamin (1994), Agambem (2009), Naive (2014), Ginzburg (2012), Hutcheon (1991), Goff (1990), Pellegrini (1999), Said (2003), Watt (1990), Schwarz (2001), Ricoeur (1994), between others.
Prose of contemporary fiction: the reflections of the military coup of 1964 in A festa, by Ivan Ângelo
Keywords: Literatura brasileira contemporânea; A festa; Ivan Ângelo; História; Ficção; Contemporary brazilian literature; History; Fiction; LINGUISTICA, LETRAS E ARTES::LETRAS